Climate-Driven Effects on NPP in the Tibetan Plateau Alpine Grasslands Diminish with Increasing Elevation - Ze Tang; Yangjian Zhang; Ming Lei; Zhaolei Li; Guang Zhao; Yao Chen; Wenquan Zhu (Remote Sensing)
Temperature and precipitation are important abiotic factors affecting net primary productivity (NPP) in grassland ecosystems. However, findings on how elevation influences the effects of these factors on NPP in alpine grasslands are not yet consistent. In addition, the impact of varied patterns of climate change on NPP sensitivity with elevation remain unclear. Therefore, alpine grassland on the Tibetan Plateau (TP) was selected to profile the spatial and temporal patterns of NPP from 2001 to 2022, and subsequently to reveal the effects of temperature and precipitation on the sensitivity of NPP with altitudinal gradient. The results showed that (1) 91% of the TP grassland experienced positive NPP trends, and the NPP trends followed a unimodal curve with elevation, with the largest mean value at 2500 m; (2) a positive correlation between precipitation and NPP dominated the grassland NPP up to an elevation of 3400 m, and a positive correlation between temperature and NPP dominated the grassland NPP above an elevation of 3400 m; (3) temperature, precipitation, and their interaction explained, on average, 21% of the temporal variation in the NPP of TP grassland, and the explanatory capacity decreased significantly with elevation; and (4) elevation, temperature, and precipitation variations together explained 35% of the NPP sensitivity of the TP grasslands. This study reveals the altitudinal characteristics of NPP in grasslands affected by climate, and reminds us to take elevation into account when carrying out grassland management.